PENGEMBANGAN BUKU AJAR ELEKTRONIK PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN UNTUK KELAS XI SMA - Fani Nurilah Febriati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
The purpose of this study are to develop electronic textbooks (e-books), describing the expediency study based on theoretical and empirical content, language and presentation, and to know the students' response to electronic textbooks (e-book). The research has been tested development is limited to 15 high school students Giki 2 Surabaya. Stages of the research is to formulate learning objectives, analyzing and learning activities, developing instructional materials, evaluation and study by 3 lecturers of biology UNESA and 2 high school biology teacher Giki 2 Surabaya, revised, tested, and revised again. The research instrument used for the study sheet lecturer and teacher and student questionnaire sheet. The results stated that the e-book on the material structure and function of plant tissue fit for use as a medium of learning according to the review of expediency criteria that combine several criteria of BSNP and the advantange of e-books. The overall results of the expediency study of the e-book shows the average value of the media presentation format, the format of the expediency of the content, and the format of language components between lecturers and teachers is 92,4%. The average yield was 95,8% of student responses. Keywords: E-book, Expediency, Structure and Function of Plant Tissue